B Cells Are Required to Generate Optimal Anti-Melanoma Immunity in Response to Checkpoint Blockade - Singh, Shubhra; Roszik, Jason; Saini, Neeraj; Singh, Vipul Kumar; Bavisi, Karishma; Wang, Zhiqiang; Vien, Long T.; Yang, Zixi; Kundu, Suprateek; Davis, Richard E.; Bover, Laura; Diab, Adi; et al. (Frontiers in Immunology, 2022)
Immunotherapies such as checkpoint blockade therapies are known to enhance anti-melanoma CD8+ T cell immunity, but only a fraction of patients treated with these therapies achieve durable immune response and disease control. It may be that CD8+ T cells need help from other immune cells to generate effective and long-lasting anti-tumor immunity or that CD8+ T cells alone are insufficient for complete tumor regression and cure. Melanoma contains significant numbers of B cells; however, the role of B cells in anti-melanoma immunity is controversial. In this study, B16 melanoma mouse models were used to determine the role of B cells in anti-melanoma immunity. C57BL/6 mice, B cell knockout (KO) C57BL/6 mice, and anti-CXCL13 antibody–treated C57BL/6 mice were used to determine treatment efficacy and generation of tumor-specific CD8+ T cells in response to PD-L1 blockade alone or in combination with TLR-7/8 activation. Both CD40-positive and CD40-negative B cells were isolated from tumors of TLR-7/8 agonist–treated wild-type mice and adoptively transferred into tumor-bearing B cell KO mice, which were treated with anti-PD-L1 and TLR-7/8 agonist. Therapeutic efficacy was determined in the presence of activated or inactivated B cells. Microarray analysis was performed on TLR-7/8–treated tumors to look for the B cell signatures. B cells and B cell chemokine CXCL13 were required to enhance the therapeutic efficacy of monotherapy with anti-PD-L1 antibody and combination therapy with anti-PD-L1 antibody plus TLR-7/8 agonist. However, B cells were not essential for anti-CTLA-4 antibody activity. Interestingly, CD40-positive but not CD40-negative B cells contributed to anti-melanoma immunity. In addition, melanoma patients’ TCGA data showed that the presence of B cell chemokine CXCL13 and B cells together with CD8+ T cells in tumors were strongly associated with improved overall survival. These results revealed the importance of B cells in the generation of effective anti-melanoma immunity in response to PD-1–PD-L1 blockade immunotherapy. Our findings may facilitate the design of more effective anti-melanoma immunotherapy.